Association of Serum YKL-40 With the Presence and Severity of Obstructive Sleep Apnea Syndrome. Issue 3 (21st September 2015) - Li, Wei; Yu, Zhen; Jiang, Chengcheng
Abstract : Objective: This study examined the association of serum YKL-40 concentrations with the presence and severity of obstructive sleep apnea syndrome (OSAS). Methods: A total of 156 patients with OSAS and 110 healthy subjects were enrolled in this study. Results: OSAS patients had significantly higher serum YKL-40 levels compared with healthy controls. Multivariable logistic regression analysis indicated that serum YKL-40 levels were an independent determinant of the presence of OSAS. Serum YKL-40 levels were significantly elevated in severe OSAS patients compared with mild and moderate OSAS patients. Spearman correlation analysis revealed that serum YKL-40 levels were correlated with the severity of OSAS. Simple linear regression analysis showed that the serum levels of YKL-40 were correlated with body mass index (BMI), homeostasis model assessment of insulin resistance (HOMA-IR), C-reactive protein (CRP), and apnea-hypopnea index (AHI) in patients with OSAS. Conclusion: Elevated serum YKL-40 levels are associated with the presence and severity of OSAS.